Low‐intensity transcranial magnetic stimulation promotes the survival and maturation of newborn oligodendrocytes in the adult mouse brain. Issue 8 (16th April 2019) - Cullen, Carlie L.; Senesi, Matteo; Tang, Alexander D.; Clutterbuck, Mackenzie T.; Auderset, Loic; O'Rourke, Megan E.; Rodger, Jennifer; Young, Kaylene M.
Abstract: Neuronal activity is a potent extrinsic regulator of oligodendrocyte generation and central nervous system myelination. Clinically, repetitive transcranial magnetic stimulation (rTMS) is delivered to noninvasively modulate neuronal activity; however, the ability of rTMS to facilitate adaptive myelination has not been explored. By performing cre‐lox lineage tracing, to follow the fate of oligodendrocyte progenitor cells in the adult mouse brain, we determined that low intensity rTMS (LI‐rTMS), administered as an intermittent theta burst stimulation, but not as a continuous theta burst or 10 Hz stimulation, increased the number of newborn oligodendrocytes in the adult mouse cortex. LI‐rTMS did not alter oligodendrogenesis per se, but instead increased cell survival and enhanced myelination. These data suggest that LI‐rTMS can be used to noninvasively promote myelin addition to the brain, which has potential implications for the treatment of demyelinating diseases such as multiple sclerosis. Main Points: The impact that low intensity repetitive transcranial magnetic stimulation (LI‐rTMS) has on cells of the oligodendrocyte lineage is stimulation frequency and cell‐stage specific. LI‐rTMS does not affect oligodendrocyte progenitor cell proliferation or density. LI‐rTMS, delivered in an intermittent theta burst pattern, promotes the survival of premyelinating oligodendrocytes and enhances myelin internode extension by newly myelinating oligodendrocytes.